2019
DOI: 10.1111/voxs.12524
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards an appropriate pathogen reduction technology for whole blood in Africa

Abstract: Adapting the INTERCEPT RBC PRT for WB The INTERCEPT PRT for RBC and WB uses amustaline (0Á2 mM) to irreversibly cross-link nucleic acids and glutathione (GSH) (20 mM for RBC and 2 mM for WB) to quench unreacted amustaline. Laboratory and clinical trial results for the RBC PRT form the basis for the WB PRT. Preliminary studies have demonstrated preservation of RBC quality in amustaline/GSH-treated WB. A Phase 1 safety trial in Côte d'Ivoire and development of a WB processing kit requiring limited electricity ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 80 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…High-income countries that have implemented NAT to screen blood donors report residual risks for TTIs to be <1 per 1 million units of blood tested [53][54][55]. In SSA countries, where NAT testing is scarce, a different scenario is observed with unsettling high residual risks for these infections reported that vary from 67 to 250 per 1 million units tested [56]. Concerns remain with emerging pathogens not routinely tested in blood banks that jeopardise the quality of blood [13].…”
Section: Hbv: Occult B Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-income countries that have implemented NAT to screen blood donors report residual risks for TTIs to be <1 per 1 million units of blood tested [53][54][55]. In SSA countries, where NAT testing is scarce, a different scenario is observed with unsettling high residual risks for these infections reported that vary from 67 to 250 per 1 million units tested [56]. Concerns remain with emerging pathogens not routinely tested in blood banks that jeopardise the quality of blood [13].…”
Section: Hbv: Occult B Infectionmentioning
confidence: 99%
“…Pathogen inactivation through different PRT in plasma and platelet are already widespread in high-income countries. However, whole blood PRTs are not yet commercially available but are presently undergoing clinical trials [55,56]. Considering the high demand for whole blood and elevated prevalences of TTIs in SSA countries, the effective use of PRT would be an opportunity to increase safe blood availability.…”
Section: Hbv: Occult B Infectionmentioning
confidence: 99%
“…In addition, a PRT using a process that does not require an illumination device and can be performed with low electricity requirements may be attractive in limited resource settings where infrastructures are under-developed and where a limited number of trained staff may be available. 32 In conclusion, our study demonstrated that the inactivation of P. falciparum to below the limit of detection can be achieved in WB units using the amustaline/GSH PRT. Development of such a pathogen reduction system may provide an opportunity to reduce the risk of TT malaria in endemic areas where current WHO recommendations assessing for donor suitability (identification of donors at the lowest risk of infection, screening of donations for parasitemia, malaria antigen or DNA) are impractical.…”
Section: Discussionmentioning
confidence: 54%
“…Development of pathogen inactivation systems for WB for these countries is thus relevant as the most transfused products are WB followed by RBC concentrates to treat life‐threatening emergencies, like massive bleeding (mostly post‐partum hemorrhage) and severe anemia (malaria related anemia in children). In addition, a PRT using a process that does not require an illumination device and can be performed with low electricity requirements may be attractive in limited resource settings where infrastructures are under‐developed and where a limited number of trained staff may be available …”
Section: Discussionmentioning
confidence: 99%
“…However, interestingly progress towards pathogen inactivation of whole blood, the general transfusion commodity in Sub-Saharan Africa, has recently been published. [15] Another paramount element is the need for standards and documentation in casu a well designed, comprehensive and operational quality system management based on an established quality culture. [16]…”
Section: Future Perspectives On Implementation Of Advanced Technologiesmentioning
confidence: 99%